COMPARATIVE STUDY OF FITTING VARIOUS LACTATION CURVE MODELS IN SAHIWAL COWS - V.B. Dongre; R.S. Gandhi (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The present investigation was carried out on 25,499 weekly test day milk yield records of first lactation pertaining to 593 Sahiwal cows spread over 49 years located at National Dairy Research Institute, Karnal, India. The comparison of three lactation curve models viz, quadratic model, gamma type function and mixed log function was made in the present investigation. Mixed log function described the best fit with highest coefficient of determination (97.9%) with lowest value of root mean square error (0.025 kg) value. The peak yield of 8.08 kg in 8thweek of lactation was observed by mixed log function. The closeness of the curves of mixed log function and gamma type function with the observed lactation curve was of the same order of magnitude. The least coefficient of determination (77.8%) was observed in quadratic model with maximum root mean square error (0.081 kg). The gamma type function when compared to mixed log function, explained low peak yield and it is recommended that this function can give best fit for the low yielding cows.